Shear stress activates monovalent cation channel transient receptor potential melastatin subfamily 4 in rat atrial myocytes via type 2 inositol 1, 4, 5‐trisphosphate receptors and Ca2+ release. (9th February 2016) - Son, Min‐Jeong; Kim, Joon‐Chul; Kim, Sung Woo; Chidipi, Bojjibabu; Muniyandi, Jeyaraj; Singh, Thoudam Debraj; So, Insuk; Subedi, Krishna P.; Woo, Sun‐Hee
Abstract : Key points: During each contraction and haemodynamic disturbance, cardiac myocytes are subjected to fluid shear stress as a result of blood flow and the relative movement of sheets of myocytes. The present study aimed to characterize the shear stress‐sensitive membrane current in atrial myocytes using the whole‐cell patch clamp technique, combined with pressurized fluid flow, as well as pharmacological and genetic interventions of specific proteins. The data obtained suggest that shear stress indirectly activates the monovalent cation current carried by transient receptor potential melastatin subfamily 4 channels via type 2 inositol 1, 4, 5‐trisphosphate receptor‐mediated Ca 2+ release in subsarcolemmal domains of atrial myocytes. Ca 2+ ‐mediated interactions between these two proteins under shear stress may be an important mechanism by which atrial cells measure mechanical stress and translate it to alter their excitability. Abstract: Atrial myocytes are subjected to shear stress during the cardiac cycle under physiological or pathological conditions. The ionic currents regulated by shear stress remain poorly understood. We report the characteristics, molecular identity and activation mechanism of the shear stress‐sensitive current ( I shear ) in rat atrial myocytes. A shear stress of ∼16 dyn cm −2 was applied to single myocytes using a pressurized microflow system, and the current was measured by whole‐cell patch clamp. In symmetrical CsCl solutions with minimal concentrations of internal EGTA, I shear showed an outwardly rectifying current–voltage relationship (reversal at −2 mV). The current was conducted primarily (∼80%) by monovalent cations but not Ca 2+ . It was suppressed by intracellular Ca 2+ buffering at a fixed physiological level, inhibitors of transient receptor potential melastatin subfamily 4 (TRPM4), intracellular introduction of TRPM4 antibodies or knockdown of TRPM4 expression, suggesting that TRPM4 carries most of this current. A notable reduction in I shear occurred upon inhibition of Ca 2+ release through the ryanodine receptors or inositol 1, 4, 5‐trisphosphate receptors (IP3 R) and upon depletion of sarcoplasmic reticulum Ca 2+ . In type 2 IP3 R (IP3 R2) knockout atrial myocytes, I shear was 10–20% of that in wild‐type myocytes. Immunocytochemistry and proximity ligation assays revealed that TRPM4 and IP3 R2 were expressed at peripheral sites with co‐localization, although they are not localized within 40 nm. Peripheral localization of TRPM4 was intact in IP3 R2 knockout cells. The data obtained in the present study suggest that shear stress activates TRPM4 current by triggering Ca 2+ release from the IP3 R2 in the peripheral domains of atrial myocytes. Key points: During each contraction and haemodynamic disturbance, cardiac myocytes are subjected to fluid shear stress as a result of blood flow and the relative movement of sheets of myocytes. The present study aimed to characterize the shear stress‐sensitive membrane current in atrial myocytes using the whole‐cell patch clamp technique, combined with pressurized fluid flow, as well as pharmacological and genetic interventions of specific proteins. The data obtained suggest that shear stress indirectly activates the monovalent cation current carried by transient receptor potential melastatin subfamily 4 channels via type 2 inositol 1, 4, 5‐trisphosphate receptor‐mediated Ca 2+ release in subsarcolemmal domains of atrial myocytes. Ca 2+ ‐mediated interactions between these two proteins under shear stress may be an important mechanism by which atrial cells measure mechanical stress and translate it to alter their excitability.